Assistência a crianças desnutridas: análise de dados do Sistema de Informação Hospitalar do Sistema Único de Saúde do Brasil Care for malnourished children: an analysis of Brazilian National Health Service Hospital Information System data - Sonia Azevedo Bittencourt; Roberta Pereira Niquini; Ana Cristina Reis; Maria do Carmo Leal (Instituto Materno Infantil de Pernambuco, 2009)
OBJETIVOS: caracterizar aspectos da assistência aos desnutridos menores de cinco anos, internados durante o ano de 2004 em hospitais conveniados ao Sistema Único de Saúde (SUS). MÉTODOS: foram analisadas as informações geográficas, demográficas, de diagnóstico e resultado da assistência, das internações hospitalares disponíveis no Sistema de Informação Hospitalar do Sistema Único de Saúde. RESULTADOS: a taxa mais alta de internação por desnutrição foi encontrada na região Nordeste. Do total de internações por desnutrição no Brasil, 36,2% foram registradas como não especificadas. A taxa de mortalidade hospitalar por desnutrição para o Brasil apresentou-se baixa, porém, mostrou-se moderada para crianças menores de seis meses e alta quando desnutrição grave foi registrada no campo de diagnóstico secundário. Para 102 municípios brasileiros a taxa de mortalidade hospitalar por desnutrição também foi alta. Merece atenção o fato de que 11,4% das crianças faleceram nas primeiras 24 horas de hospitalização, e a complementação do tratamento ambulatorial foi indicada em 3,7% das Autorizações de Internação Hospitalar. CONCLUSÕES: mostram-se necessárias a valorização pelos profissionais de saúde da avaliação do estado nutricional e seu correto registro como causa de internação, bem como, a integração e a hierarquização dos diferentes níveis de atenção à criança desnutrida. OBJECTIVES: to characterize features of care provided for malnourished children aged under five years admitted to hospitals affiliated to the Brazilian National Health Service in 2004. METHODS: geographical, demographic data and information relating to diagnosis, results of care and admission to hospital available on the Brazilian National Health Service's Hospital Information System were analyzed. RESULTS: the highest rate for admission to hospital for malnutrition was found in the Northeast region. Of all admissions to hospital for malnutrition in Brazil as a whole, 36.2% were registered as non-specific. The hospital mortality rate for malnutrition in Brazil was low, but moderate for children aged under six months and high when severe malnutrition was registered in the secondary diagnosis field. The hospital mortality rate for malnutrition was also high in 102 Brazilian municipalities. It is worth noting that 11.4% of children died within the first 24 hours following admission to hospital and the complementary outpatient treatment was recommended in 3.7% of Hospital Admissions Authorizations. CONCLUSIONS: the study revealed the importance of health workers recognizing the value of the nutritional status evaluation and correctly registering this as the cause of admission to hospital, and also integrating and ordering the various levels of care for malnourished children.